Streseman and Politics of Weimar Republic - Turner, Henry Ashby 1932-2008 (Princeton University Press, 1965)
Largely because Gustav Stresemann’s fame rests on his accomplishments as Germany’s foreign minister during the Weimar Republic, little has been written about his equally important part in the domestic politics of Germany. Beginning with the emergence of the Republic in the autumn of 1918, Professor Turner charts Stresemann’s rise in only three and a half years from member of the German Reichstag to Chancellor of the Republic. Using information drawn from Stresemann’s private papers, and concentrating on the interrelation of Stresemann’s domestic and foreign policies, the author presents here a well-balanced study of the complex man who, sometimes by sheer will alone, held the new German Republic together.Originally published in 1963.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905
Description based on online resource; title from PDF title page (publisher's Web site, viewed Sep. 08, 2016)
Keywords: Stresemann, Gustav -- 1878-1929; Statesmen -- Germany -- Biography; Politik; Deutschland; Biografie